INNOVATIVE APPROACH TO THE EFFECTIVE ORGANIZATION OF LESSONS ON THE TECHNOLOGY OF A COMPREHENSIVE EDUCATIONAL SCHOOL - Mukhamedova Kh.B. (Scholar Express Journal, 2022)
The article discusses the modern requirements for the education of young people, in the light of which not only basic, but also extra-curricular education of secondary school students is important. The pedagogical principles on which extracurricular activities of students should be based are considered, the conclusion is drawn on the need to use innovative approaches to organizing extracurricular activities. The stages of introducing innovative technologies are described, several technologies are listed for organizing extracurricular activities of secondary school students
Keywords: Extracurricular Education; Extracurricular Activities Of Students; Innovative Pedagogical Technologies.